'Value for money' and the restaurant experience: a case study of supply and demand stakeholders. Issue 1 (2016) - Alonso, Abel Duarte; Sakellarios, Nikolaos; Jones, Chris; Cseh, Leonard; Cooper, Sandra J.
Using the case of a training restaurant open to paying guests, this study compares the perceptions of two groups of stakeholders with regard to different factors of the dining experience. The first group represents the supply side and is composed of 73 students involved in the preparation and delivery of menu dishes, while the demand side consists of 222 guests of the training restaurant. Both groups' level of agreement was similar when they identified gaps regarding the restaurant's performance in terms of décor, design, lighting and background music. The groups, however, differed in their perceptions of other elements, most notably regarding the selection of beverages, and the entertainment aspect of the dining experience (e.g., deboning fish in front of guests), with students clearly in lesser agreement. Overall, the study's findings demonstrate that involving different groups of stakeholders to evaluate the restaurant's performance could potentially enhance the dining experience.